THE DECISION-MAKING EFFORT OF STRATEGIC PLANNING CV. DUA SEKAWAN ACCU - Juhandi Juhandi (International Journal of Economy, Education and Entrepreneurship, 2022)
This planning has been acknowledged as a function or initial step in the management field, and it applies to all levels of management. It also defines the goals of an organization as well as the procedure for determining how the management system will achieve its goals and how it will achieve its goals. Moreover, it defines the objectives of the management system. Therefore, direct research methods are utilized throughout the entirety of this study. The methodology applied in this research consisted of employing qualification and descriptive methodologies, both of which aimed to achieve a deeper level of comprehension regarding the findings of this investigation, specifically the data that was compiled in the form of words and documentation. Decision-makers must use exceptional cases and possibly deal with generic rules. Strategic planning is thought to be a method for managing change that can be avoided as a result, as well as a method for dealing with environmental complexities frequently associated with using the organization's interests. However, this is also a method for exploring the complexity of the internal environment caused by the various needs of each organization's work units